Tracing leadership: the ECB's 'whatever it takes' and Germany in the Ukraine crisis. Issue 5 (28th July 2020) - Schoeller, Magnus G.
Abstract: Political scientists face problems when assessing a leader's impact: how can we know that a policy outcome or institutional change is caused by leadership? This article argues that in addition to relying on comparisons and counterfactuals, we need to trace the causal mechanisms by which leadership affects outcomes. Therefore, the article proposes a way to trace leadership and applies it to two cases of EU crisis management: the European Central Bank's role in announcing Outright Monetary Transactions in the eurozone crisis, and Germany's role in shaping the EU's response to the Ukraine crisis. Systematic process-tracing shows that both actors provided leadership 'by default'. However, while the ECB had to combine the provision of knowledge with unilateral action in order to overcome the eurozone crisis, Germany could use manifold bargaining-based strategies and thus became the EU's de facto agenda setter and main representative in managing the Ukraine crisis.